1993
DOI: 10.1128/mcb.13.7.4077
|View full text |Cite
|
Sign up to set email alerts
|

Cell-type-specific function of the C-type natriuretic peptide gene promoter in rat anterior pituitary-derived cultured cell lines.

Abstract: The promoter function of the human C-type natriuretic peptide (CNP) (23,38), and then was identified in rat and human brains (19,28). CNP shares considerable sequence homology with ANP and BNP, especially within the 17-residue ring portion formed by a disulfide bond between two cysteine residues. According to the cloned cDNA and genes for CNP from various species (17,19,28,40,41), the structure of CNP is highly conserved among species, and rat, porcine, and human CNP-22 are actually identical. CNP seems to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…This last observation is particularly interesting in light of the reported mouse vs. human differences in CNP response to LPS since the bacterial protein is known to signal through the NF-␤ pathway [95]. In addition, although both species possess at least one GC box in the promoter, the human CNP promoter possesses two GC boxes in tandem to constitute the 'GC-rich' DNA-binding site as described above [62]. This could represent a crucial difference in CNP transcriptional regulation between rodent and human.…”
Section: Cnp Genementioning
confidence: 93%
See 4 more Smart Citations
“…This last observation is particularly interesting in light of the reported mouse vs. human differences in CNP response to LPS since the bacterial protein is known to signal through the NF-␤ pathway [95]. In addition, although both species possess at least one GC box in the promoter, the human CNP promoter possesses two GC boxes in tandem to constitute the 'GC-rich' DNA-binding site as described above [62]. This could represent a crucial difference in CNP transcriptional regulation between rodent and human.…”
Section: Cnp Genementioning
confidence: 93%
“…The consensus sequence for Ap-2 was similarly without effect. Furthermore, a 70 kD putative regulatory protein, identified by its binding to the GC-rich region, did not match the MWs for either Sp-1, CREB or Ap-2 [62]. On the contrary, Thompson et al [88] have very recently shown evidence using electrophoretic mobility shift assays (EMSA) that both Sp-1 and Sp-3 bind as a complex to the putative GC-rich regulatory site in the proximal Nppc promoter.…”
Section: Putative Transcription Factorsmentioning
confidence: 99%
See 3 more Smart Citations